Nanomedicine and Addictive Disorders: A New Approach With Cannabinoids - Giménez, Virna Margarita Martín; Menéndez, Sebastián García; Manucha, Walter (Current Pharmaceutical Design, 2022)
Background: Most cannabinoids usually present several limitations when evaluating their clinical use, mainly related to the side effects they may cause at the central nervous system and other levels. In this regard, nanotechnology applied to the development of pharmacotherapeutic nanoformulations has become an attractive tool that allows taking advantage of the beneficial properties of multiple drugs while minimizing or avoiding their undesirable side effects. Nanotechnology is a relatively recent scientific field that involves the study, manipulation, development, and characterization of drug delivery systems at the nanoscale (1 to 1000 nm; 1 nm= 1x10-9 m). Usually, the physicochemical properties of matter at the nanoscale are significantly different compared to the matter at the macroscale, which provides several advantages over conventional therapeutic alternative types of organic and inorganic drug delivery nanosystems. Posology, size, composition, surface properties, and different physicochemical characteristics may directly or indirectly influence their pharmacodynamic and pharmacokinetic behavior and, consequently, their biomedical use. Purpose of Review: This mini-review summarizes the main recent findings on nanomedical strategies and applications for cannabinoid encapsulation, raising the possibility of transferring these advances to the therapy of addictions. Highlights Standpoints: The nano therapy significantly improves the pharmacokinetic and pharmacodynamic behavior of multiple active pharmaceutical ingredients with different limitations and disadvantages, thus enhancing the therapeutic compliance of patients. In general, cannabinoids loaded in nanoformulations offer greater efficacy, lower toxicity and more controlled/prolonged release than cannabinoids in free form.
Keywords: Addictions